A domain adaptive hybrid genetic algorithm and its verification in security service function chain orchestration - Xiaohui YAO; Qing LI; Kunkun SUN (Dianxin kexue)
Faced with changeful network demands,users have increasingly higher requirements for traditional network.Features such as flexibility,scalability and ease of use have become essential elements of modern network.A domain adaptive hybrid genetic algorithm (DAHGA) was proposed,which could be applied to the security service chain arrangement of cloud data center tenants,to achieve automatic loading and activation of tenant cloud security services and policies,to meet tenant cloud security “customization on demand” requirements.And conducts experimental comparison research on the effective placement efficiency of each VNF on the cloud security service chain orchestration was carried out,which fully validated the proposed algorithm.Effectiveness provides a reference and reference for the realization of cloud business non-destructive security service chain orchestration technology.